Analytical Application of 3-Hydroxy-3-m-tolyl-1-mchlorophenyltriazene as Metallochromic Indicator for Complexometric Determination of Molybdenum(VI) - KHAN, SABA; KHANAM, REHANA (Asian Journal of Chemistry, 2010)
A new reagent 3-hydroxy-3-m-tolyl-1-m-chlorophenyltriazene has been used for the spectrophotometric and complexometric determination of Mo(VI). Spectrophotometric determination is carried out at 408 nm, in the pH range 2.0-3.0. Beer's law is obeyed in the range (1 to 6) × 105 M. The values of molar absorptivity and Sandell's sensitivity are 7184.7 dm3 mol-1 cm-1 and 13.35 ng cm-2, respectively. It has also been used as metallochromic indicator in complexometric titration of Mo(VI), where the colour change is from light greenish yellow to colourless at the end point. The best results are obtained in pH range between 2-3. Satisfactory results have been obtained in the entire studied range.